Case report: Successful treatment of OXA-23 Acinetobacter baumannii neurosurgical infection and meningitis with sulbactam-durlobactam combination therapy - Snowdin, Jacob W.; Mercuro, Nicholas J.; Madaio, Michael P.; Rawlings, Stephen A. (Frontiers in Medicine, 2024)
Meningitis caused by Acinetobacter species is a rare complication of neurosurgical procedures, although it is associated with high morbidity and mortality. Carbapenemresistant Acinetobacter is particularly difficult to treat, considering the limited selection and tolerability of effective antimicrobials. Sulbactam-durlobactam was approved by the FDA in 2023 for treatment of hospital-acquired and ventilator-associated pneumonia due to susceptible strains of Acinetobacter, including carbapenem-resistant Acinetobacter baumannii. Here, we present a case of carbapenem-resistant Acinetobacter baumannii neurosurgical infection and meningitis successfully treated with sulbactam-durlobactam combination therapy. Introduction: Neurosurgical infection and meningitis are rare but serious complications following cranial procedures. In nosocomial infections, resistant Gram-negative bacilli such as Acinetobacter baumannii are often implicated and are associated with mortality upwards of 40% (1). With an already limited antimicrobial armamentarium against carbapenemresistant A. baumannii (CRAB), medical management becomes difficult considering the efficacy, tolerability, and pharmacokinetics of available antibiotics in the setting of central nervous system (CNS) infections. A multifaceted approach that includes supportive care, surgical source control, combination antimicrobial therapy, and extensive rehabilitation are needed to achieve successful treatment and recovery. In the most recent iteration of the IDSA nosocomial meningitis and ventriculitis guidelines, the only treatment recommended for CRAB is colistin which does not readily enter the cerebrospinal fluid (CSF) (2). Efficacy data for treatment of CNS infections due to CRAB with parenteral antibiotic therapy is limited. We report a case of CRAB craniectomy site infection with concomitant meningitis successfully treated with IV sulbactam-durlobactam (SUL-DUR) combination therapy.